Archives, recordkeeping, and social justice - Saucier, Renée; Duff, Wendy M.; Wallace, David A. 1961-; Flinn, Andrew 1965- (Routledge Studies in Archives, 2020)
Archives, Record-keeping and Social Justice expands the burgeoning literature on archival social justice and impact. Illuminating how diverse factors shape the relationship between archives, recordkeeping systems, and recordkeepers, the book depicts struggles for different social justice objectives. Discussions and debates about social justice are playing out across many disciplines, fields of practice, societal sectors, and governments and yet one-dimension cross-cutting these actors and engagement spaces has remained unexplored: the role of recordkeeping and archiving. To clarify and elaborate this connection, this volume provides a rigorous account of the engagement of archives and records - and their keepers - in struggles for social justice. Drawing upon multidisciplinary praxis and scholarship, contributors to the volume examine social justice from historical and contemporary perspectives and promote impact methodologies that align with culturally responsive, democratic, Indigenous and transformative assessment. Underscoring the multiplicity of transformative social justice impacts influenced by record making, recordkeeping, and archiving, the book presents nine case studies from around the world that link the past to the present and offer pathways towards a more just future. Archives, Record-keeping and Social Justice will be essential reading for researchers and students engaged in the study of archives, truth and reconciliation processes, social justice and human rights. It should also be of great interest to archivists, records managers and information professionals"--